Exploring the Substrate Scope of the Bacterial Phosphocholine Transferase AnkX for Versatile Protein Functionalization. (21st August 2019) - Ochtrop, Philipp; Ernst, Stefan; Itzen, Aymelt; Hedberg, Christian
Abstract: Site‐specific protein functionalization has become an indispensable tool in modern life sciences. Here, tag‐based enzymatic protein functionalization techniques are among the most versatilely applicable approaches. However, many chemo‐enzymatic functionalization strategies suffer from low substrate scopes of the enzymes utilized for functional labeling probes. We report on the wide substrate scope of the bacterial enzyme AnkX towards derivatized CDP‐choline analogues and demonstrate that AnkX‐catalyzed phosphocholination can be used for site‐specific one‐ and two‐step protein labeling with a broad array of different functionalities, displaying fast second‐order transfer rates of 5×10 2 to 1.8×10 4 m −1 s −1 . Furthermore, we also present a strategy for the site‐specific dual labeling of proteins of interest, based on the exploitation of AnkX and the delabeling function of the enzyme Lem3. Our results contribute to the wide field of protein functionalization, offering an attractive chemo‐enzymatic tag‐based modification strategy for in vitro labeling. Abstract : Not picky ! The recently discovered phosphocholine transferase AnkX exhibits a broad substrate scope for functionalized CDP‐choline analogues that can be used for versatile protein functionalization. We report a new, flexible dual‐protein‐labeling strategy, in combination with the hydrolase Lem3, that uses two slightly different octapeptide recognition tags.